Невладините организации како одговор и коректив на директивноста на системите - Donev, Dejan (Аз-Буки, Скопје (Филозофско друштво на Македонија), 2007)
It’s no doubt about that, that the culture is our determinator, none the less for our society which is producer of it. The present time is also determinated with informatics chaos, which directs us to reconsidering of that determination as unavoidable in process of valorization of validity every human existence. We also all agree with the fact that the human been is fundamental part of society which is in the process of reconsideration and revalorization and destroying of some basic ethical, esthetical and, as a consequence of that, also of some cultural values, his (existence and identity) is putted in situation to not be asked: what kind of culture he needs to approve his own existence, and, by that, his is not any more in situation to be asked as a producer of culture. Putted in this kind of situation, to look after the answer to this basic question of his existence as a human been, he become more and more aware of the fact that the culture of society to which he belongs, especially because of incapableness of that society to restore the order of values, that society less and less is able to offer the culture which will be response of his needs as a human been. Actually hi is faced with the culture which only goal is surviving of the system. So, it’s out of mind to ask ourselves how and why the NGO became a room for correction of that way of usage of culture. It’s also no doubt about that the NGO became way of response of the needs-desire of every human been to realize it selves as a human through the culture.
NGO as a Response to and a Corrective to the Directiveness of State-Systems
Keywords: correction, NGO, ethics, human existance